Teaching leadership : innovative approaches for the 21st century - Pillai, Rajnandini; Stites-Doe, Susan; Bass, Bernard M. (Emerald Publishing Limited : Information Age Pub., 2003)
A collection of papers which examine the reinvention of leadership education for the 21st century.
Keywords: Leadership -- Study and teaching.; Education -- Leadership.; Educational psychology.; Educational strategies and policy.; elektronické knihy; electronic books